Triplicated P-wave measurements for waveform tomography of the mantle transition zone - Staehler, S; Sigloch, K; Nissen-Meyer, T (European Geosciences Union, 2012)
Triplicated body waves sample the mantle transition zone more extensively than any other wave type, and interact strongly with the discontinuities at 410 km and 660 km. Since the seismograms bear a strong imprint of these geo-dynamically interesting features, it is highly desirable to invert them for structure of the transition zone. This has rarely been attempted, due to a mismatch between the complex and band-limited data and the (ray-theoretical) modelling methods. Here we present a data processing and modelling strategy to harness such broadband seismograms for finite-frequency tomography. We include triplicated P-waves (epi-central distance range between 14 and 30°) across their entire broadband frequency range, for both deep and shallow sources. We show that is it possible to predict the complex sequence of arrivals in these seismograms, but only after a careful effort to estimate source time functions and other source parameters from data, variables that strongly influence the waveforms. Modelled and observed waveforms then yield decent cross-correlation fits, from which we measure finite-frequency traveltime anomalies. We discuss two such data sets, for North America and Europe, and conclude that their signal quality and azimuthal coverage should be adequate for tomographic inversion. In order to compute sensitivity kernels at the pertinent high body wave frequencies, we use fully numerical forward modelling of the seismic wavefield through a spherically symmetric Earth. © Author(s) 2012. CC Attribution 3.0 License.